2013
DOI: 10.3923/pjbs.2013.1811.1814
|View full text |Cite
|
Sign up to set email alerts
|

Sub-acute Effects of Ethanol Extract of Sarcocephalus latifolius Root on Some Physiologically Important Electrolytes in Serum of Normal Wistar Albino Rats

Abstract: Sarcocephalus latifolius (Synonym, Nauclea latifolia) is a shrub commonly seen in the South East of Nigeria. It is widely applied as herbal remedy in the treatment of various illnesses. The effect of ethanol extract of the root of the plant on some serum electrolytes was studied. A total of thirty Wistar albino rats were used to determine serum concentrations of K+, Ca2+, Cl- and HCO3-. The animals were divided into six groups of five rats each. Five groups labeled A, B, C, D and E, were administered orally wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…It has been reported that electrolytes have an important role in muscle contraction and relaxation ( Shrimanker and Bhattarai, 2020 ). The similar study has been carried out by Enemor and Okaka, 2013 , in which they found the beneficial effects of ethanolic extract of Sarcocephalus latifolius root on Na and K in rats.…”
Section: Discussionsupporting
confidence: 66%
“…It has been reported that electrolytes have an important role in muscle contraction and relaxation ( Shrimanker and Bhattarai, 2020 ). The similar study has been carried out by Enemor and Okaka, 2013 , in which they found the beneficial effects of ethanolic extract of Sarcocephalus latifolius root on Na and K in rats.…”
Section: Discussionsupporting
confidence: 66%
“…This study was designed to determine the possible development of toxicity due to a single (orally administered) dose of the ethanol root extract of Sarcocephalus latifolius in apparently healthy (non-induced) wistar albino rats by monitoring the serum status of liver enzymes, bilirubin, cholesterol and triglyceride, which often are common indices for estimating the margin of safety in the use of herbal remedies. Studies are a follow up on our earlier findings (Enemor et al, 2013.…”
Section: Introductionmentioning
confidence: 75%
“…This is important in order to establish a margin of safety in the use of the plant and its products. Some analyses had earlier been conducted in line with this objective, including effects on serum electrolytes (Enemor and Okaka, 2013), sub-acute effects on kidney function markers , subacute effects on liver function markers . In this study we evaluate the possible effect of a relatively single high dose of the root extract for any sudden development of toxicity or a progressive development over a few days following the administration.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium ion is a cation of the intracellular fluid which plays a vital role in muscle contraction [28]. It is normally excreted by the kidneys, so disorders that impair kidney function can lead to hyperkalaemia [29]. The most common cause of high potassium is kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of BASO even at higher doses investigated on the renal function biomarkers suggests that the normal functionality of the nephrons at the tubular and glomerular levels were not altered. Bicarbonate buffer system is the most important amongst blood buffers when the pH of the blood is considered [33]. Chloride ion is a major extra cellular anion.…”
Section: Discussionmentioning
confidence: 99%